2018
DOI: 10.1177/1350650117753915
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of subsynchronous vibration in floating ring bearings

Abstract: Floating ring bearings are popular among turbochargers due to their simplicity and reliability. The disappearance of subsynchronous vibration with the increase of shaft speed in a low oil-supplied pressure floating ring bearing is reported by Hatakenaka and Yanai. This finding may help eliminate the noise and decrease the loss of turbochargers. This work aims to explain this phenomenon in the low oil-supplied floating ring bearing using computational fluid dynamic. Steady computational fluid dynamic calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Obviously, the static and dynamic characteristics of the bubbly oil lubrication bearing will be influenced by factors such as the void fraction. Therefore, the new bubbly oil lubrication technology has been concerned and studied by researchers and found that shaft vibration can be suppressed, frictional power consumption is reduced [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the static and dynamic characteristics of the bubbly oil lubrication bearing will be influenced by factors such as the void fraction. Therefore, the new bubbly oil lubrication technology has been concerned and studied by researchers and found that shaft vibration can be suppressed, frictional power consumption is reduced [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. 12 constructed a computational fluid dynamics (CFD) calculation method to predict the performance of floating ring bearings and validate the air entrainment effect. Vibration characteristics are investigated through the transit CFD calculation with the mesh motion method using discrete Fourier transform analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Aerostatic bearings are widely employed in gas turbines, grinding machines, and high-precision positioning systems due to the properties of low friction, low heat conduction, environmentally friendly operation, and long life. 15 The static performance of aerostatic bearings is a significant aspect of its application. Their performance is significantly affected by many factors such as machining tolerances, 6 configuration structure, 7,8 feed system type, 913 bearing geometrical and operational parameters, 1418 and grooves.…”
Section: Introductionmentioning
confidence: 99%